Epidemiology of risk factors of various morphological types of age-related cataract in eastern region of Nepal - Gupta, Namrata; Lavaju, Poonam; Shah, Sangeeta; Badhu, Badri Prasad (Birat Journal of Health Sciences, 2021)
Introduction: Age related cataract is the leading cause of preventable blindness globally, with multifactorial risk factors. Multiple mechanism contributes to the progressive loss of lens transparency.Objective: The purpose of this study is to determine the risk factors for different morphological types of senile cataract in eastern region of Nepal.Methodology:  A hospital based cross sectional study was conducted in a tertiary care hospital. Four hundred patients aged ≥ 50 years with senile cataract attending eye out patient department for one year were enrolled and divided into two groups based on Lens Opacities Classification System (LOCS) III grading. Group A consisted of ‘no-moderate’ cataract and group B consisted of ‘severe’ cataract. The parameters studied were age, gender, education, occupation, smoking, alcohol consumption, diabetes and hypertension, body mass index and use of topical or oral medication. Statistical analysis was conducted to find an association of various parameters to different morphological type of cataract.Results: The mean age of presentation was 61±9.07 years. Male to female ratio was 1:02. Group A had 154 and group B 246 patients respectively. Statistically significant association was seen between older age group and severe cataract (p